NEW DATA ON THE CHEMICAL PROPERTIES OF KIMBERLITE FROM THE UDACHNAYA PIPE (YAKUTIA) - Khitrov V.G.; Zinchuk N.N.; Kotel'nikov D.D. (My University, 1988)
The Udachnaya pipe consists of two associated bodies, an eastern and western, that are in contact to a depth of between 250 to 270 m, but are separated at greater depths. The cluster analysis of the chemical composition of kimberlites from the two bodies of the Udachnaya pipe enabled us to examine their geochemistry, and revealed the main features of the emplacement subsequent change of the eastern and western bodies. We found that the chemical zoning is more weakly expressed in the eastern body, but is characterized by an anomalous upward increase in melanocraticity. In the western body the zoning is more distinct and systematic. We find there an almost regular vertical replacement of magnesian-ferruginous compositions by SiO2-Al2O3 compositions, a trend opposite to that in the eastern body. These differences ultimately reflect the origin of the eastern and western bodies.